Information dissemination, market efficiency and the frequency of transactions - Barry Goldman, M.; Sosin, Howard B. (Journal of Financial Economics, 1979)
Casual observers of the New York Stock Exchange are often dumbfounded by the frenetic behavior of its participants. If asked how such chaos generates accurate prices many academicians would reply that the ability to transact frequently is a virtue since it promotes prompt information dissemination and therefore market efficiency. However, in contrast to the NYSE where, during trading hours, trades may be consumated almost continuously, the Paris Stock Exchange trades each security only a handful of times a day. This continental contrast in market structure led us to reexamine the role of speed in markets. We have discovered that if sufficient uncertainty surrounds the dissemination of information, frequent transacting may be deleterious to market efficiency. In fact, in our paradigm we are able to show that our measure of market efficiency may be maximized when there is a unique, non-zero time interval between consecutive trades. The measure of efficiency used throughout the paper is minus the mean squared error. This measure was chosen to focus upon the information content of prices at times when they are posted (i.e., at times of tâtonnements). For this purpose we ignore costs of illiquidity and costs associated with obsolete information that would occur between tâtonnements. In this restricted sphere, maximazation of our efficiency measure is consistent with maximizing Social Pareto Optimality.